2011
DOI: 10.1021/es2007726
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modeling Adsorption of PAHs to Carbon Nanotubes Over a Six Order of Magnitude Wide Concentration Range

Abstract: Understanding the interactions between organic contaminants and carbon nanomaterials is essential for evaluating the materials' potential environmental impact and their application as sorbent. Although a great deal of work has been published in the past years, data are still limited in terms of compounds, concentrations, and conditions investigated. We applied a passive sampling method employing polyoxymethylene (POM-SPE) to gain a better understanding of the interactions between polycyclic aromatic hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 23 publications
4
116
1
1
Order By: Relevance
“…Therefore, the emission of LMW-PAHs was more influenced by flowrate than by the different electrochemical reactions of anode and cathode; additionally, the emission of Nap was more influenced by flowrate than those of the other PAH species. The PAHs in the anode or cathode emission gas should be associated with the desorption of the PAHs adsorbed on the carbon materials of PEMFC during operation, although the graphitic structure of carbon materials might have strong interactions with PAHs through π-π interactions (Kah et al, 2011) and PAHs are relatively easier to adsorb on than to desorb from the surface of carbon blacks (Moninot, 2010).…”
Section: Effect Of Flowrate On Pemfc Pahs and Pahs-associated Bap Eq mentioning
confidence: 99%
“…Therefore, the emission of LMW-PAHs was more influenced by flowrate than by the different electrochemical reactions of anode and cathode; additionally, the emission of Nap was more influenced by flowrate than those of the other PAH species. The PAHs in the anode or cathode emission gas should be associated with the desorption of the PAHs adsorbed on the carbon materials of PEMFC during operation, although the graphitic structure of carbon materials might have strong interactions with PAHs through π-π interactions (Kah et al, 2011) and PAHs are relatively easier to adsorb on than to desorb from the surface of carbon blacks (Moninot, 2010).…”
Section: Effect Of Flowrate On Pemfc Pahs and Pahs-associated Bap Eq mentioning
confidence: 99%
“…In the case of trichloroethylene it was found that carbon nanotubes increase the time constant of the slow desorption mechanism (τ 2 ) ( Figure 4a), which is assumed to be mainly related to π-π interactions between CNTs and the C=C bond present in C 2 HCl 3 [14,17]. Due to the removal of doi: 10.7243/2050-1323-3-2 amorphous carbon after the water plasma treatment, and the corresponding surface area enhancement that provides more space for solute adsorption, the desorption time of the wp-CNTsQF sample increased with respect to that of untreated CNTs (Figure 4a, Table 2).…”
Section: Adsorption/desorption Studiesmentioning
confidence: 99%
“…The characteristics of CNTs suggest that they have strong interaction with organic molecules through non-covalent forces, hydrogen bonds, π-π interactions in, for instance, polycyclic aromatic hydrocarbons (PAHs) [17], electrostatic forces and van der Waals forces. The main interactions responsible for the adsorptions of organic compounds by CNTs are: hydrophobic effect, π-electron donor−acceptor (π-EDA) bonds and hydrogen bonds [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…LM, usually applicable to describe monolayer adsorption on homogeneous surfaces, is unsuitable for CNTs because the presence of high-energy sorption sites such as defects, functional groups, and interstitial or groove regions between CNT bundles [22] makes the CNTs' surfaces heterogeneous. FM, an empirical equation, failed to describe the sorption behavior of organic pollutants on CNTs over a wide concentration range [23].…”
Section: Sorption Isothermsmentioning
confidence: 99%